Dosing and Therapeutic Conduct in Administration Sessions in Substance-Assisted Psychotherapy: A Systematized Review - Thal, Sascha; Wieberneit, Michelle; Sharbanee, Jason; Skeffington, Petra; Bruno, Raymond; Wenge, T.; Bright, Stephen (SAGE, 2023)
While the potential of serotonergic psychedelics and related substances as adjuncts in substance-assisted psychotherapy (SAPT) has been investigated for the treatment of several disorders, evidence for the appropriate therapeutic conduct in administration sessions is sparse. In this article, we discuss the current evidence for best therapeutic practice during administration sessions with serotonergic psychedelics and entactogens as adjuncts to psychotherapy. We conducted a systematized review of the literature following PRISMA guidelines. PsycINFO, MEDLINE, and Cochrane Library databases were searched. Clinical trials, treatment manuals, study protocols, qualitative studies, case studies, descriptive studies, opinion papers, reviews, book chapters, and conference proceedings published until February 1, 2022 were retrieved. The final synthesis included k = 82 sources. Information about substances, dosages, number of administration sessions, issues that are common for clients, different types of experiences, music, and therapeutic conduct was summarized, compared, and critically discussed. The effects different therapeutic models, methods, techniques, and more complex interventions each have on the therapeutic outcome have not been investigated by means of rigorous research. Most of the available evidence we retrieved was anecdotal limiting any conclusive statements regarding appropriate therapeutic conduct during administration sessions. Consequently, essential components of therapeutic interventions remain largely tentative, necessitating systematic investigation.